Improving Productivity through the Design of a quality management system based on the ISO 22000:2018 standard - Contreras-Rivera, Robert; Alarcon-Ventura, Katicsa; Vilcahuaman-Sanabria, Raul; Garay-Torres, Jose; Rua-Pomahuacre, Silvia; Ipince-Antunez, Daniel; Benites-Gutierrez, Miguel (LACCEI, 2024)
The objective of this research is to demonstrate, through the design of a Quality Management System based on the ISO 22000:2018 Standard, the increase in the productivity of the Molinera company. This is because, in this organization, whose function is the production of flour, pasta and cookies derived from wheat; Low productivity has been evident due to the absence of standardization in its processes and insufficient systematization in food safety management. This is how, when carrying out a baseline diagnosis analyzing the initial productivity and comparing it with that obtained after the prediction of estimation values ​​of the Design of the Quality Management system for the twelve-month interval, an increase of 33.4% was obtained. of productivity. Likewise, regarding the efficiency and effectiveness indicators, which improved significantly. Converting this Design into an optimal alternative for improvement in organizations.